Some fixed point results and their applications on integral type contractive condition in fuzzy metric spaces - Vishal Gupta; Naveen Mani; Rajinder Sharma; Adesh Kumar Tripathi (Boletim da Sociedade Paranaense de Matemática, 2022)
The role of Fuzzy topology in logic programming and algorithm has been recognized and applied on various programs to and more accurate result. In particular, topological methods are employed in order to obtain fixed point semantics for logic programs. In this paper, we prove some fixed point theorems in fuzzy metric spaces. As an application, some consequence theorems are given in support of our result.